Digital Instructional Leadership: A New Model of Supervision in Developing Teachers’ Competence and Performance in Madrasahs - Shinta Dhuhrotul Himaya; Moh Harun Al-Rosid (Ainara Journal (Jurnal Penelitian dan PKM Bidang Ilmu Pendidikan), 2026)
The rapid development of digital technology demands a transformation of educational leadership in madrasahs; however, many principals still focus primarily on administrative tasks, resulting in suboptimal technology-based instructional supervision. This study aimed to analyze the role of Digital Instructional Leadership as a new supervision model for developing teacher competence and performance in Islamic junior high schools (Madrasah Tsanawiyah). The study employed a qualitative approach using a case study design at MTsN 7 Banyuwangi. Data were collected through in-depth interviews, participant observation, and document analysis involving the principal and ten teachers. Data analysis followed the Miles and Huberman model, including data reduction, data display, conclusion drawing, and verification. The findings revealed that the implementation of Digital Instructional Leadership significantly improved teachers’ professional competence, enhanced the quality of academic supervision, and fostered a more disciplined, transparent, and accountable work ethic. Teachers became more creative in designing digital learning materials, implementing technology-based instruction, and conducting systematic evaluations. These findings indicate that Digital Instructional Leadership transforms academic supervision from a formal administrative activity into an effective professional development strategy that is relevant to the needs of madrasahs in the digital era. The study also highlights the importance of strengthening technology-based leadership policies to sustainably improve learning quality.